The effect of board directors from countries with different genetic diversity levels on corporate performance - Manthos D. Delis; Chrysovalantis Gaganis; Iftekhar Hasan; Fotios Pasiouras (Bank of Finland, 2015)
We link genetic diversity in the country of origin of the firms' board members with corporate performance via board members' nationality. We hypothesize that our approach captures deep-rooted differences in cultural, institutional, social, psychological, physiological, and other traits that cannot be captured by other recently measured indices of diversity. Using a panel of firms listed in the North American and U.K. stock markets, we find that adding board directors from countries with different levels of genetic diversity (either higher or lower) increases firm performance. This effect prevails when we control for a number of cultural, institutional, firm-level, and board member characteristics, as well as for the nationality of the board of directors. To identify the relationship, we use as instrumental variables for our diversity indices the migratory distance from East Africa and the level of ultraviolet exposure in the directors' country of nationality.
URN:NBN:fi:bof-201508181353
Keywords: 330